Bioanalytics for Influenza Virus-Like Particle Characterization and Process Monitoring - Carvalho, Sofia B.; Silva, Ricardo J. S.; Sousa, Marcos F. Q.; Peixoto, Cristina; Roldão, António; Carrondo, Manuel J. T.; Alves, Paula M. (Frontiers in Bioengineering and Biotechnology, 2022)
Virus-like particles (VLPs) are excellent platforms for the development of influenza vaccine candidates. Nonetheless, their characterization is challenging due to VLPs unique biophysical and biochemical properties. To cope with such complexity, multiple analytical techniques have been developed to date (e.g., single-particle analysis, thermal stability, or quantification assays) most of which are rarely used or have been successfully demonstrated for being applicable for virus particles’ characterization. In this study, several biophysical and biochemical methods have been evaluated for thorough characterization of monovalent and pentavalent influenza VLPs from diverse groups (A and B) and subtypes (H1 and H3) produced in insect cells using the baculovirus expression vector system (IC-BEVS). Particle size distribution and purity profiles were monitored during the purification process using two complementary technologies - nanoparticle tracking analysis (NTA) and tunable resistive pulse sensing (TRPS). VLP surface charge at the selected process pH was also assessed by this last technique. The morphology of the VLP (size, shape, and presence of hemagglutinin spikes) was evaluated using transmission electron microscopy. Circular dichroism was used to assess VLPs thermal stability. Total protein, DNA and baculovirus content were also assessed. All VLPs analyzed exhibited similar size ranges (90-115 nm for NTA and 129-141 nm for TRPS), surface charges (average of -20.4 mV), and morphology (pleomorphic particles resembling influenza virus) exhibiting the presence of HA molecules (spikes) uniformly displayed on M1 protein scaffold. Our data shows that HA titers and purification efficiency in terms of impurity removal and thermal stability were observed to be particle dependent. This study shows robustness and generic applicability of the tools and methods evaluated, independent of VLP valency and group/subtype. Thus, they are most valuable to assist process development and enhance product characterization.